Gastrulation in an annual killifish: Molecular and cellular events during germ layer formation in Austrolebias. Issue 11 (24th March 2017) - Pereiro, Luisa; Loosli, Felix; Fernández, Juan; Härtel, Steffen; Wittbrodt, Joachim; Concha, Miguel L.
Abstract : Background : Comparative studies beyond the traditional model organisms have been instrumental in enhancing our understanding of the conserved and derived features of gastrulation, a fundamental process in which the germ layers are specified and shaped to form the body axis. Here, we analyzed gastrulation in a vertebrate group with an extreme mode of early development, the annual killifish.Results: Gastrulation in annual killifish of the genus Austrolebias takes place after the initially dispersed deep blastomeres congregate to form the so‐called reaggregate. Cells from the early reaggregate do not appear to form part of any recognizable axial embryonic structure and are possibly extraembryonic. In contrast, later reaggregate cells become engaged in morphogenetic transformations indicative of a process of gastrulation and axis formation. The expression of brachyury and goosecoid suggests that gastrulation takes place in a compressed blastopore‐like structure with an organizer region displaced to one end. No collective cell internalization proper of blastopore architecture is observed, though, and it appears that gastrulation primarily involves the reorganization of individual cells.Conclusions: The unique mode of gastrulation in annual killifish demonstrates that a process so ancient and fundamental to ontogenesis can have striking morphogenetic variations nonpredicted from the sole examination of model species. Developmental Dynamics 246:812–826, 2017 . © 2017 Wiley Periodicals, Inc. Key findings: By combining morphology, gene expression analysis, cell labeling, and in vivo imaging in embryos of the genus Austrolebias, we provide a first description of the process of gastrulation for an annual killifish. Gastrulation in Austrolebias takes place after the initially dispersed deep blastomeres congregate to form the so‐called reaggregate. Cells of the early reaggregate do not appear to form part of any recognizable axial embryonic structure and, thus, are possibly extraembryonic. In contrast, cells from later stages of reaggregation (stages RIII to RV) become progressively engaged in morphogenetic transformations, indicative of a process of gastrulation and early axis formation. The expression of brachyury and goosecoid suggests that gastrulation in Austrolebias takes place in a compressed blastopore‐like structure with an organizer region displaced to one end. However, no sign of collective cell internalization is observed, and it appears that centripetal movements and events of single‐cell reorganization shape the cellular reaggregate during gastrulation. At later stages of development, the domains of goosecoid and brachyury expression separate along the anterior‐posterior axis as the reaggregate elongates, in a manner similar to the process of axis elongation described in other vertebrate embryos.